PEMANFAATAN INTERNET OF THINGS (IOT) DALAM PENGEMBANGAN SMART EDUCATION PADA SEKOLAH MENENGAH DI INDONESIA - Amiroh Kamilah Namora Lubis; Sendi Senjaya Putra; Trivena Imanuela Siampa Rumbino; Ari Apriyansa; Louren Vania Surbakti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study aims to examine the utilization of the Internet of Things (IoT) in the development of smart education in secondary schools in Indonesia. The background of this study is based on the increasing need for digital transformation in education, which is not only focused on the use of technological devices but also on the development of an intelligent, adaptive, and data-driven learning ecosystem. The main problems addressed in this study are how IoT is utilized to support smart education, what challenges arise in its implementation, and what strategies can be applied to ensure effective and sustainable IoT implementation in Indonesian secondary schools. This study employed a Systematic Literature Review (SLR) method by analyzing various national and international scientific articles published between 2020 and 2026. The literature was reviewed based on topic relevance, research focus, forms of IoT implementation, benefits, challenges, and strategies for developing smart education. The findings indicate that IoT plays a role in supporting smart classrooms, automatic attendance systems, classroom environment monitoring, school security, facility management, project-based learning, and data-driven decision-making. However, IoT implementation in Indonesia is still largely focused on technical and operational aspects, such as device automation and school administration. The main challenges identified include limited internet infrastructure, teacher readiness, digital literacy, device costs, data security, and unequal facilities across regions. Therefore, the development of IoT-based smart education needs to be implemented gradually, adaptively, inclusively, and sustainably by considering the integration of technology, pedagogy, school management, and human resource readiness. ABSTRAK Penelitian ini bertujuan untuk mengkaji pemanfaatan Internet of Things (IoT) dalam pengembangan smart education pada sekolah menengah di Indonesia. Latar belakang penelitian ini didasarkan pada meningkatnya kebutuhan transformasi digital pendidikan yang tidak hanya berfokus pada penggunaan perangkat teknologi, tetapi juga pada pembentukan ekosistem pembelajaran yang cerdas, adaptif, dan berbasis data. Permasalahan utama dalam penelitian ini adalah bagaimana IoT dimanfaatkan dalam mendukung smart education, apa saja tantangan implementasinya, serta strategi apa yang dapat dilakukan agar penerapan IoT di sekolah menengah Indonesia berjalan efektif dan berkelanjutan. Penelitian ini menggunakan metode Systematic Literature Review (SLR) dengan menganalisis berbagai artikel ilmiah nasional dan internasional yang diterbitkan pada rentang tahun 2020–2026. Literatur dikaji berdasarkan relevansi topik, fokus penelitian, bentuk implementasi IoT, manfaat, tantangan, dan strategi pengembangan smart education. Hasil kajian menunjukkan bahwa IoT berperan dalam mendukung smart classroom, absensi otomatis, monitoring lingkungan kelas, keamanan sekolah, manajemen fasilitas, pembelajaran berbasis proyek, serta pengambilan keputusan berbasis data. Namun, penerapan IoT di Indonesia masih banyak berfokus pada aspek teknis dan operasional, seperti otomasi perangkat dan administrasi sekolah. Tantangan utama yang ditemukan meliputi keterbatasan infrastruktur internet, kesiapan guru, literasi digital, biaya perangkat, keamanan data, serta kesenjangan fasilitas antarwilayah. Oleh karena itu, pengembangan smart education berbasis IoT perlu dilakukan secara bertahap, adaptif, inklusif, dan berkelanjutan dengan memperhatikan integrasi antara teknologi, pedagogi, manajemen sekolah, dan kesiapan sumber daya manusia.